Tuesday

March 3, 2015

March 3, 2015

Posted by **Anonymous** on Saturday, October 29, 2011 at 7:53pm.

f(-6) =

- MATH -
**Damon**, Saturday, October 29, 2011 at 7:57pmassume you mean x^2 + 4

(-6)^2 + 4

36+4

40

- MATH -
**ALISON**, Saturday, October 29, 2011 at 7:58pm-8.

Plug in -6 for x and solve.

**Answer this Question**

**Related Questions**

Math - Assume f(x) = x2 + 3. Find the functional value requested. f(-5) =

ALGEBRA - Assume f(x) = x2 + 4. Find the functional value requested. f(-3) =

ALGEBRA - Assume f(x) = x2 + 3. Find the functional value requested. f(-7) =

ALGEBRA - Assume f(x) = x2 + 3. Find the functional value requested. f(-7)

Math - Find the functional values requested in the problem; h(x)=5x-4 (a) h(0...

math - find the functional values requested in the problem F(x)=x^2-25t (a)F(5t...

ALGEBRA - Find the functional values requested in the problem. h(x)=3 x-1 (a) h(...

ALGEBRA - Find the functional values requested in the problem. h(x)=5 x-1

Math - How will I work this problem? Find the functional values requested in the...

Math - Find the requested value. f(-4)for f(x)={6x, if x ¡Ü -1 f(-4)for f(x)=x...